Aplikasi Realiti Maya Dalam Pendidikan : Makmal Kimia Maya (MaKiM) - Rusnida, Romli (2002)

(untitled)
The existence of information era triggered by the revolution in information technology has the ability to bring about tremendous improvement in our education system. This rapid improvement is closely related to the use of the most recent and sophisticated technology. Virtual Reality(VR) technology has great potential to be integrated into the education system. This research on MaKiM is based largely on challenges faced by both the chemistry teachers and the students in their conventional style of teaching and learning especially in understanding the experiments and the associated process. Hence MaKiM is developed to add value to the existing education system. Research methods include literature review, data collection, prototype design, prototype development, prototype testing, data analysis and documentation. Several hypotheses are also created and tested to enhance this research. The 3D Web Engine software, Wild Tangent and 3D Studio MAX 3.1 have been used in the prototype development of MaKiM. Prototype testing is done on 8 selected schools located within the district of Kota Setar and Kubang Pasu. Apart from the questionnaire, pre and post testing are performed to accumulate the data. Quantitative and inferential analyses are performed, as well as inferential analysis i.e. the t-test that is used to determine the significance of analysis at 0.05 level. The analysis provides evidence that MaKiM or the use of VR technology in education can improve the understanding, particularly in areas that the realities are hard to grasp. MaKiM in a way creates an interesting learning environment for students. It is also hoped that MaKiM that uses a high technological approach can facilitate the implementation of Smart School.